2023
DOI: 10.3389/fpubh.2022.1059248
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres susceptibility to environmental arsenic exposure: Shortening or lengthening?

Abstract: Maintaining telomere length plays a crucial role in regulating cellular life span. Telomere lengthening or shortening is one of the important biomarkers which could predict the preceding or present diseases. Meanwhile, the impact of environmental arsenic exposure on telomere length has increasingly concerned. Although previous studies demonstrated the effects of arsenic on telomere length, the findings were unclear on whether telomere shortens or lengthens by arsenic exposure. Thus, this manuscript summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Interestingly, phytoremediation can also mitigate the negative consequences of heavy metals (Yan et al, 2020). There is extensive literature linking heavy metals to telomere length changes (Pawlas et al, 2015;Zota et al, 2015;Borghini et al, 2016;Fillman et al, 2016;Wai et al, 2020;Wai et al, 2023). Since heavy metal exposure elevates ROS (Flora, 2002;Cuypers et al, 2010;Jaishankar et al, 2014), one intriguing possibility is the heavy metal content of the lunar regolith simulant (Long-Fox et al, 2023) causes increased genome oxidation, which in turn leads to telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, phytoremediation can also mitigate the negative consequences of heavy metals (Yan et al, 2020). There is extensive literature linking heavy metals to telomere length changes (Pawlas et al, 2015;Zota et al, 2015;Borghini et al, 2016;Fillman et al, 2016;Wai et al, 2020;Wai et al, 2023). Since heavy metal exposure elevates ROS (Flora, 2002;Cuypers et al, 2010;Jaishankar et al, 2014), one intriguing possibility is the heavy metal content of the lunar regolith simulant (Long-Fox et al, 2023) causes increased genome oxidation, which in turn leads to telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Telomeres at the ends of chromosomes comprise repeat sequences (TTAGGG) that shorten with each cell division because of the nature of the DNA replication machinery. 20 They protect against chromosomal damage by preventing chromosome–chromosome fusions and degradation and subsequently maintaining genome integrity. 21 Telomere shortening occurs in normal somatic cells following each cell division.…”
Section: Mechanisms Of Cellular Senescencementioning
confidence: 99%
“…Epidemiological studies reported both lengthening and shortening of telomeres in individuals chronically exposed to As(III) [ 85 ]. A possible mechanism for As(III)-induced telomere lengthening involves the upregulation of the telomerase catalytic subunit (hTERT) and telomere binding proteins such as TRF1 and TRF2, subunits of the telomere sheltering complex [ 85 ]. Thus, As(III) may partially contribute to carcinogenesis by promoting telomere elongation, which is crucial for the maintenance and viability of human cancer cells.…”
Section: How Arsenic and Antimony Cause Genotoxicitymentioning
confidence: 99%
“…Paradoxically, As(III)-induced downregulation of both hTERT and TRF2 was also observed and associated with telomere shortening. Since telomere sequences are rich in guanine, which is particularly sensitive to oxidative damage, it has been proposed that As(III) may cause telomere attrition through oxidative stress [ 85 ]. Importantly, 4 μM As(III) induced increased ROS levels in glioblastoma cells (U87 line) followed by translocation of telomerase from the nucleus to the cytoplasm, telomere shortening, and accumulation of γH2AX (histone H2AX variant phosphorylated on Ser139, which serves as a sensitive marker of DNA damage and repair) that co-localized with TRF1, strongly suggesting that the telomeres are sites of As(III)-generated DNA damage in an oxidative stress-dependent manner [ 86 ].…”
Section: How Arsenic and Antimony Cause Genotoxicitymentioning
confidence: 99%